The Role of Public Investment in Driving Economic Growth in Developing Countries - Rio Rinaldy; Aji Soleman; Alfin Firnanto; Nur Syahrani Setiawati; Vani Rahmayani (Return : Study of Management, Economic and Bussines, 2026)
Public investment is one of the main instruments of fiscal policy in encouraging economic growth in developing countries. However, its effectiveness often shows results that vary between countries. This study aims to analyze the role of public investment in economic growth by emphasizing the aspects of investment amount, management efficiency, and expenditure composition. The approach used is qualitative descriptive by utilizing secondary data from several developing countries. The results of the analysis show that countries with higher levels of public investment tend to have better economic growth, although the relationship is not linear. Investment management efficiency has proven to be a key factor that determines success, where countries with higher levels of efficiency are able to produce more optimal growth. In addition, the composition of investment also plays an important role, especially the allocation in the infrastructure sector which correlates with an increase in economic performance. These findings confirm that the success of public investment is not only determined by the size of the budget, but also by the quality of management and the accuracy of allocation. Therefore, fiscal policies in developing countries need to be focused on improving the efficiency and quality of public spending to achieve sustainable economic growth.